Pengaruh Air Rebusan Daun Sirih Hijau terhadap Penyembuhan Luka Perineum di Puskesmas Beutong 2024 - Herawati Herawati; Basaria Manurung (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Postpartum infection is likely to originate from infected perineal suture wounds. These suture wounds are caused by episiotomy or infected incisions and due to tears in the birth canal or perineal tears. This study aims to determine the Effect of Green Betel Leaf Boiled Water in Accelerating Perineal Wound Healing at the Beutong Ateuh Health Center, Beutong Ateuh Banggalang District, Nagan Raya Regency, Aceh Province in 2024. This type of research is a quasi-experimental research method with a Post test with control group design. The population is all postpartum mothers who experience grade I-II perineal wounds at the Beutong Ateuh Health Center, Beutong Ateuh Banggalang District, Nagan Raya Regency, Aceh Province, as many as 22 people. The number of samples used was 22 people obtained using the Total sampling technique. The data analysis technique used the paired sample t-test value. The results obtained in this study were from 22 respondents, there was a difference in the effect of green betel leaf decoction in accelerating the healing of perineal wounds in the intervention group and the control group with the independent sample t test obtained results for the value of p = 0.000 meaning p <0.05.